Prevalence of Prostate Problems among Adults in Obio/Akpor Local Government Area (LGA) of Rivers State - Nwankwo, Grace A.; Asukwu, Uche G.; Igwe, Dominic, U.; Ugwuoke, Anthony C.; Ojide, Rita Ngozika; Gbaduo , Celestina C (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
This study was carried out to provide information on the prevalence of prostate problems among adults in Obio/Akpor Local Government Area. A cross-sectional descriptive design was employed for this study. Four research questions were posed to guide the study while one research hypothesis postulated to guide the study was tested at 0.05 level of significance. The population of the study was 1,010 adult males aged forty years or older. The entire population was used as the sample size. The instrument for data collection was a self-developed and pretested Data Collection Schedule Form (DCSF).Data collected were analyzed using descriptive statistics of frequency, percentage and Chi square inferential statistic. The results showed that the prevalence of prostate problems was 32.3%. BPH had a prevalence of 57.4%, CA-Prostate had 19.3% and Prostatitis had 23.3%. The prevalence increased with age; those 70 years and above had the highest prevalence of 48.8%; P > .05 (P = .616) at .05 level of significance indicating no significant association in the prevalence of prostate problems among the different age cohorts. It was concluded that there was a high prevalence of prostate problems in the studied population. This implies that one in three apparently normal men 40 years and above had one of the prostate problems. This calls for a concerted effort to reverse this trend. Researchers should embark on research on the causes, risk factors, diagnosis and management of the conditions. This can be achieved by government and other funders making grants available to researchers.